2017
DOI: 10.1161/circresaha.116.308434
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Noncoding RNAs as Biomarkers of Cardiovascular Disease and Injury

Abstract: The discovery of thousands of noncoding RNAs (ncRNAs) has expanded our view on mammalian genomes and transcriptomes, as well as their organization and regulation. Accumulating evidence on aberrantly regulated ncRNAs, including short microRNAs, long ncRNAs and circular RNAs, across various heart diseases indicates that ncRNAs are critical contributors to cardiovascular pathophysiology. In addition, ncRNAs are released into the circulation where they are present in concentration levels that differ between health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
276
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 329 publications
(282 citation statements)
references
References 144 publications
(226 reference statements)
2
276
0
4
Order By: Relevance
“…Serum and plasma miRNAs are probably the most suitable source for clinical application as sample collection is quick, simple, and reproducible. Indeed, miRNAs are remarkably stable and resistant in the blood and long-term storage or freezing/thawing cycles do not seem to cause problems (28, 29). Interestingly, circulating miRNAs are protected from endogenous high levels of RNase activity in the blood since they are linked to carriers in vesicles or non-vesicular forms (30).…”
Section: Micrornasmentioning
confidence: 99%
“…Serum and plasma miRNAs are probably the most suitable source for clinical application as sample collection is quick, simple, and reproducible. Indeed, miRNAs are remarkably stable and resistant in the blood and long-term storage or freezing/thawing cycles do not seem to cause problems (28, 29). Interestingly, circulating miRNAs are protected from endogenous high levels of RNase activity in the blood since they are linked to carriers in vesicles or non-vesicular forms (30).…”
Section: Micrornasmentioning
confidence: 99%
“…Previous studies have shown that lncRNA can be used as a competitive endogenous RNA (ceRNA) and interacts with miRNAs, participates in the regulation of expression of target genes, and plays an important role in the progression of cardiovascular disease [6]. Zhou et al demonstrated XIST promoted myocardial infraction by targeting miR-130a-3p [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Pitx2c gene, expressed in the left compartment of the heart at embryonic stage, and in the left atrium, pulmonary vein, and right ventricle after birth, can inhibit Shox2 expression through direct interaction with its promoter (Ai et al 2006;Nowotschin et al 2006;Wang et al 2010Wang et al , 2014Ammirabile et al 2012) and indirectly regulates Shox2 expression through the inhibitory effects of microRNAs (miR-1792 and miR-106b-25) (Viereck and Thum 2017). The latter phenomenon is due to the expression of Pitx2c in the left heart compartment; thus, the Shox2 expression is restricted in SAN tissue of the right atrium, and the SAN differentiation and development are activated via Shox2-inhibited Nkx2.5 expression.…”
Section: Fig 2 Schematic Representation Of Shox2 and Shox2 Proteinsmentioning
confidence: 99%